Green Building Implementation at Adiwiyata Mandiri Elementary School in Malang City - Putri Herlia Pramitasari; Suryo Tri Harjanto (ESE International Journal (Environmental Science and Engineering), 2021)
Green School Festival and Adiwiyata award are the government's efforts to build the character of the nation's next generation for improving the quality of the environment based on education, participation, and sustainability. The application of green building principles in school buildings is equally important to support environmental quality improvement. Therefore, this study is focused on evaluating the fulfillment of green building criteria at Adiwiyata Mandiri Elementary School in Malang City. The analytical descriptive qualitative research method was carried out in this study by taking the object of study at SDN Tunjungsekar 1 and SD Insan Amanah Malang City. The results showed that the fulfillment of the green building criteria at the Adiwiyata Mandiri Elementary School in Malang City has not been optimal in fulfilling the principles of green buildings, both related to site management, energy efficiency, water, materials, improving the quality of indoor health and comfort, also building environmental management.